ISLAMIC MEDIA LITERACY AND ENVIRONMENTAL JUSTICE EDUCATION: NARRATIVES, ACTIVISM, AND CURRICULUM DESIGN - Ivan Nurseha; Farida Huseynova (MIYAH: Jurnal Studi Islam, 2025)
This study investigates the intersection of Islamic media literacy and environmental justice education by exploring how Islamic narratives and values can inform critical media engagement and ecological consciousness. Drawing on interdisciplinary frameworks from Islamic studies, environmental pedagogy, and media literacy education, the research examines the role of Islamic discourse in shaping eco-activism and sustainable curriculum practices. Through qualitative content analysis of Islamic media sources ranging from sermons, social media campaigns, to digital da'wah platforms this study identifies recurring themes of environmental stewardship (khal?fah), balance (m?z?n), and moral accountability (taqw?) in ecological messaging. It further analyzes educational interventions and curriculum models that integrate these values to cultivate environmentally responsible citizens in Muslim-majority contexts. The findings reveal that Islamic media literacy, when aligned with environmental justice education, fosters a holistic pedagogical approach that combines spiritual, ethical, and ecological dimensions. This research contributes to emerging scholarship on faith-based environmental education and offers practical insights for curriculum designers, educators, and religious leaders in promoting sustainable development through Islamic educational paradigms.